Teledentistry: A Boon Amidst COVID-19 Lockdown—A Narrative Review. (17th February 2021) - Deshpande, Shantanu; Patil, Devendra; Dhokar, Amol; Bhanushali, Parin; Katge, Farhin
Abstract : The recent spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated coronavirus disease (COVID-19) has caused widespread public health concerns. Despite huge efforts to contain the disease spread, it is still on the rise because of the community spread pattern of this infection. In order to prevent the community spread, a nationwide lockdown was implemented, due to which many restrictions were imposed on movements of citizens within the country. Since the dental professionals were at the forefront of acquiring the infection, the majority of the dental clinics were shut for routine dental procedures. Only emergency treatment was provided to the patients. However, due to restrictions in movement, it was difficult for the patients to visit the clinics for routine check-ups. This was overcome by the advancements in technology which has a major impact on medicine. Due to increased usage of smartphones and related software applications, the clinical data exchange was facilitated between patients and clinicians which has been termed as "teledentistry." Teledentistry is a combination of telecommunications and dentistry, involving the exchange of clinical information and images for dental consultation and treatment planning. This technology served as a boon for the dentists to manage dental emergencies during the lockdown period. This narrative review discusses teledentistry and its applications in general and specialty dental practice amidst the COVID-19 lockdown.